UPAYA MENINGKATKAN HASIL BELAJAR IPA TEMA 6 MENGGUNAKAN MODEL PBL PADA SISWA KELAS V SDN 2 KATERBAN TAHUN AJARAN 2021/2022 - Nurul Hidayah; Kartika Chrysti Suryandari; Wahyudi Wahyudi (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2022)
The study aimed to improve natural science learning outcomes about ‘’Heat Transfer’’ applied problem based learning to fifth grade students. It was classroom action research carried out in three cycles. The subjects were teachers and students of fifth grade at SDN 2 Katerban. The data were qualitative and quantitative. Data collection techniques used observation, interviews, and tests. The data validity used triangulation of sources and triangulation of techniques. Data analysis were data reduction, data presentation, and drawing conclusions. The results indicated that problem based learning improved natural science learning outcomes about ‘’Heat Transfer’’. The percentages of students’ mastery learning were 86.2% in the first cycle, 87.05% in the second cycle, and 94.82% in the third cycle. It concludes that the application of problem based learning improves natural science learning outcomes about ‘’Heat Transfer’’ to fifth grade students of SDN 2 Katerban in academic year of 2021/2022